ANALISIS PENGETAHUAN PERKOPERASIAN, KEMAMPUAN MANAJERIAL, DAN KOMPETENSI KEWIRAUSAHAAN TERHADAP KINERJA PENGURUS KOPERASI KABUPATEN INDRAGIRI HULU - Drun Ibat; Zulfadil Zulfadil; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of cooperative knowledge, managerial ability, and entrepreneurial competence of cooperative management in Indragiri Hulu Regency. The population of this study includes all cooperative administrators in Indragiri Hilir Regency, amounting to 64 people.. Primary data were collected using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using multiple linear regression analysis with the help of the SPSS program. The sampling technique that has been selected is to use the Slovin formula. The results showed that: 1) Cooperative knowledge had a positive and significant effect on the performance of the cooperative management in Indragiri Hulu Regency, 2) the managerial ability of the cooperative management had a positive and significant effect on the performance of the cooperative management in Indragiri Hulu Regency, 3). Entrepreneurial competence of cooperative management has a positive and significant effect on the Performance of Cooperative Management in Indragiri Hulu Regency, 4), the Effect of Cooperative Knowledge, Managerial Ability and Entrepreneurship Competence together have a positive and significant effect on the Performance of Cooperative Management in Indragiri Hulu Regency with a strong influence value.Keywords: Cooperative Knowledge, Managerial Ability, Entrepreneurship Competence, Management Performance